Ni3Fe / Ni3ZnC0.7 composite material, preparation method and application of Mg-based hydrogen storage material
By preparing Ni3Fe/Ni3ZnC0.7 composite materials, the problem of slow high-temperature kinetics of MgH2 was solved, achieving efficient hydrogen absorption and desorption and excellent cycle stability of Mg-based hydrogen storage materials, thus improving the catalytic effect.
Patent Information
- Application Number
- CN202511126197.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-12
- Publication Date
- 2025-11-11
AI Technical Summary
Existing magnesium-based hydrogen storage material MgH2 suffers from high hydrogen release temperature and slow kinetic properties, and the impact of element substitution on the hydrogen storage performance of non-stoichiometric Ni3ZnC0.7 carbides in MgH2 has not been thoroughly studied.
Ni3Fe/Ni3ZnC0.7 composite material was prepared by vacuum filtration and calcination to form a three-dimensional interwoven nanotube and small particle structure. The nanotubes are randomly oriented and have a bamboo-like structure. Some nanotubes are embedded with fine particles to catalyze the hydrogen absorption and desorption reaction of MgH2. The catalyst was uniformly dispersed by ball milling.
It significantly improves the hydrogen absorption and desorption kinetics and cycle stability of MgH2, lowers the reaction energy barrier, accelerates the hydrogen absorption and desorption process, and enhances the overall performance of Mg-based hydrogen storage materials.
Smart Images

Figure CN120920036A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrogen storage catalyst materials technology, and particularly to a Ni3Fe / Ni3ZnC catalyst. 0.7 Composite materials and their preparation methods, and applications of Mg-based hydrogen storage materials. Background Technology
[0002] Magnesium-based hydrogen storage alloys have attracted widespread attention due to their high hydrogen storage capacity and low cost. MgH2, as one of the most widely studied hydrogen storage materials, has also attracted widespread attention due to its high theoretical hydrogen storage capacity (7.6 wt% H2) and low cost. However, it suffers from problems such as high hydrogen desorption temperature and slow kinetic properties.
[0003] In recent years, alloying, nano-sizing, and catalyst addition have been widely used to improve the hydrogen storage performance of MgH2. Among these methods, catalyst addition offers the advantages of both low cost and significant effectiveness. Among transition metal, transition metal oxide, transition metal carbide, and transition metal sulfide catalysts, transition metal carbide catalysts exhibit relatively greater advantages.
[0004] Studies have shown that, compared to stoichiometric carbides, non-stoichiometric carbides exhibit superior performance in the catalytic hydrogen storage process of MgH2 due to their unique lattice defects and electronic structure, thus possessing greater development advantages.
[0005] Published research to date (https: / / doi.org / 10.1016 / j.jma.2022.07.004) indicates that nonstoichiometric Ni3ZnC 0.7 Carbides can significantly improve the hydrogen storage performance of MgH2. Based on this research, non-stoichiometric Ni3ZnC... 0.7 MS / Ni3ZnC prepared by improving the carbide structure 0.7 Composite materials (https: / / doi.org / 10.1007 / s12598-024-02943-y) also improve the hydrogen storage performance of MgH2 to some extent. However, elemental substitution has a significant impact on the non-stoichiometric performance of Ni3ZnC. 0.7 The effect of carbides on the hydrogen storage performance of MgH2 has not been studied in depth. Summary of the Invention
[0006] To overcome the above technical problems, the purpose of this invention is to provide a Ni3Fe / Ni3ZnC 0.7 The composite material and its preparation method, as well as the application of Mg-based hydrogen storage materials, are presented. The material and its preparation method are characterized by simple preparation process, and the catalyst has the characteristics of simple morphology and excellent catalytic effect.
[0007] The technical solution adopted in this invention is:
[0008] A Ni3Fe / Ni3ZnC 0.7 The composite material consists of a large number of three-dimensionally interwoven nanotubes and surrounding small particles. The nanotubes are randomly oriented and have a bamboo-like structure. Some nanotubes are embedded with fine particles. The length of the nanotubes is 500-600 nm, the diameter is 30-100 nm, and the size of the small particles is 20-60 nm.
[0009] It is easily and uniformly dispersed when added to MgH2; these structures enable the composite material to react with MgH2 and Ni3Fe / Ni3ZnC during hydrogen adsorption / desorption cycles. 0.7 In-situ reactions generate multicomponent catalysts, such as Mg2Ni / Mg2NiH4 and Zn / MgZn2, which act as "hydrogen pumps" to accelerate the hydrogen absorption and desorption reactions. The presence of carbon materials promotes uniform catalyst dispersion and prevents MgH2 agglomeration. Simultaneously, the small amount of Fe generated improves the Mg-H bond energy and charge distribution. This catalyst exhibits a simple morphology and excellent catalytic performance.
[0010] Ni3Fe / Ni3ZnC was obtained by vacuum filtration and calcination. 0.7 Composite materials.
[0011] A Ni3Fe / Ni3ZnC 0.7 A method for preparing composite materials includes the following steps;
[0012] (1) Mix nickel acetate, ferrous acetate, zinc acetate and N,N-dimethylformamide and stir magnetically to obtain mixed solution A;
[0013] (2) Terephthalic acid, triethylamine and N,N-dimethylformamide are mixed and magnetically stirred to obtain mixed solution B;
[0014] (3) Mix the two solutions obtained in step (1) and step (2) and stir to obtain solution C;
[0015] (4) The C solution obtained in step (3) is vacuum filtered and washed multiple times with N,N-dimethylformamide;
[0016] (5) The precursor obtained in step (4) is calcined, and the calcined product is naturally cooled to obtain Ni3Fe / Ni3ZnC. 0.7 Composite materials.
[0017] In step (1), the molar ratio of nickel acetate, ferrous acetate, and zinc acetate is 2:1:1, and the total molar amount is 15 mmol. It is dissolved in 125 ml of N,N-dimethylformamide (DMF). The mass ratio of nickel acetate to N,N-dimethylformamide is 1:(80-90), the mass ratio of ferrous acetate to DMF is 1:(180-200), and the mass ratio of zinc acetate to DMF is 1:(170-180). The magnetic stirring time is 0.5-1 h.
[0018] In step (2), the molar ratio of terephthalic acid to triethylamine is 1:(1-2), the total molar amount is 24.25 mol, and it is dissolved in 100 ml of N,N-dimethylformamide. The mass ratio of terephthalic acid to N,N-dimethylformamide is 1:(60-65), the mass ratio of triethylamine to N,N-dimethylformamide is 1:(60-63), and the magnetic stirring time is 0.5-1 h.
[0019] In step (3), the magnetic stirring time is 0.5 to 1 hour.
[0020] In step (4), the vacuum filtration time is 8 to 12 hours, and the sample is washed with N,N-dimethylformamide 3 to 5 times.
[0021] In step (5), the calcination temperature is 700-800℃, the holding time is 8-10h, and the calcination atmosphere is argon.
[0022] The Ni3Fe / Ni3ZnC 0.7 The composite material is applied to hydrogen storage catalyst materials, providing effective technical support for the practical application of magnesium-based hydrogen storage materials. The Ni3Fe / Ni3ZnC composite material... 0.7 The composite material, used as a catalyst, is ball-milled and mixed with magnesium hydride powder to form a magnesium-based hydrogen storage material.
[0023] The Ni3Fe / Ni3ZnC 0.7 Composite materials constitute 2.5 wt%–7.5 wt% of magnesium-based hydrogen storage materials as catalysts;
[0024] During the ball milling process, the material-to-ball ratio is 30:1, the ball milling speed is 500 rpm, and the ball milling time is 10 hours.
[0025] The beneficial effects of this invention are:
[0026] This invention uses vacuum filtration and calcination to prepare a catalyst additive, Ni3Fe / Ni3ZnC, to enhance the hydrogen storage performance of magnesium hydride. 0.7 The preparation method is simple and the cost is low.
[0027] This preparation method is a simple vacuum filtration and calcination process. The advantage of this method is that it achieves Ni3Fe / Ni3ZnC at a relatively low cost. 0.7 The catalyst is synthesized efficiently. This structure can effectively catalyze the hydrogen absorption and desorption process of magnesium hydride, reduce the reaction energy barrier, accelerate the hydrogen absorption and desorption kinetics and improve cycle stability, thereby significantly improving the overall performance of Mg-based hydrogen storage materials.
[0028] The present invention provides a catalyst additive, Ni3Fe / Ni3ZnC, to enhance the hydrogen storage performance of magnesium hydride. 0.7 The composite material consists of a large number of three-dimensionally interwoven nanotubes and surrounding small particles. The nanotubes are randomly oriented and have a bamboo-like structure. Some nanotubes are embedded with fine particles. The morphology is simple and has a relatively good catalytic effect.
[0029] This invention adds this catalyst to MgH2, and by ball milling, the catalyst can be uniformly dispersed on the surface of MgH2, thereby obtaining better catalytic performance, and solving the problem of uneven catalyst dispersion. Attached Figure Description
[0030] Figure 1 The Ni3Fe / Ni3ZnC prepared in this invention 0.7 X-ray diffraction pattern of the composite material.
[0031] Figure 2 The Ni3Fe / Ni3ZnC prepared in this invention 0.7 Scanning electron microscope image of the composite material.
[0032] Figure 3 The graph shows the hydrogen absorption kinetics of the three Mg-based composite materials obtained in Examples 1, 2, and 3 at 80°C.
[0033] Figure 4 The graph shows the hydrogen desorption kinetics of the three Mg-based composite materials obtained in Examples 1, 2, and 3 at 300°C.
[0034] Figure 5 The MgH2-5wt%Ni3Fe / Ni3ZnC obtained in Example 1 0.7 Cyclic retention rate of composite materials at 400℃. Detailed Implementation
[0035] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0036] The instruments and equipment used and their uses are as follows in the following embodiments:
[0037] Vacuum filtration equipment: SHB-IIIS, for sample separation;
[0038] Tube furnace: OTF-1200X, sample calcination;
[0039] X-ray diffractometer: ShimadzuXRD-7000, for sample phase analysis;
[0040] Scanning electron microscope: JEOL JSM-7610F, sample morphology analysis;
[0041] Transmission electron microscope: FEI-TALOS-F200X, sample morphology analysis;
[0042] Planetary ball mill: XQM-2, for sample ball milling;
[0043] Test equipment: Sieverts-type, hydrogen storage performance test.
[0044] Example 1
[0045] (1) Mix 7.5 mmol nickel acetate, 3.75 mmol ferrous acetate, 3.75 mmol zinc acetate with 125 ml N,N-dimethylformamide and stir magnetically for 0.5 h to obtain mixed solution A;
[0046] (2) Mix 9 mmol of phthalic acid, 2.125 ml of triethylamine and 100 ml of N,N-dimethylformamide and stir magnetically for 0.5 h to obtain mixed solution B;
[0047] (3) Mix the two solutions obtained in step (1) and step (2) and stir for 1 hour to obtain solution C;
[0048] (4) The C solution obtained in step (3) was vacuum filtered for 10 hours and washed three times with N,N-dimethylformamide.
[0049] (5) The precursor obtained in step (4) is calcined at a temperature of 700℃ for 10 hours under an argon atmosphere. The calcined product is then allowed to cool naturally to obtain Ni3Fe / Ni3ZnC. 0.7 Composite materials.
[0050] Contains 5 wt% Ni3Fe / Ni3ZnC 0.7 Preparation of Mg-based hydrogen storage materials based on composite catalysts:
[0051] Take 0.2g of the Ni3Fe / Ni3ZnC prepared in this invention 0.7The composite material and 3.8 g of MgH2 powder were loaded into a ball mill jar at a ball-to-material ratio of 30:1 and ball-milled at 500 rpm for 10 h to finally obtain a Ni3Fe / Ni3ZnC mixture containing 5 wt%. 0.7 The Mg-based hydrogen storage material of the composite catalyst is designated as MgH2-5wt%Ni3Fe / Ni3ZnC. 0.7 And used for hydrogen storage performance testing.
[0052] Example 2
[0053] (1) Mix 7.5 mmol nickel acetate, 3.7 mmol ferrous acetate, 3.7 mmol zinc acetate with 100 ml N,N-dimethylformamide and stir magnetically for 0.5 h to obtain mixed solution A;
[0054] (2) Mix 9 mmol of phthalic acid, 2.125 ml of triethylamine and 100 ml of N,N-dimethylformamide and stir magnetically for 0.5 h to obtain mixed solution B;
[0055] (3) Mix the two solutions obtained in step (1) and step (2) and stir for 1 hour to obtain solution C;
[0056] (4) The C solution obtained in step (3) was vacuum filtered for 10 hours and washed three times with N,N-dimethylformamide.
[0057] (5) The precursor obtained in step (4) is calcined at a temperature of 800℃ for 10 hours under an argon atmosphere. The calcined product is then allowed to cool naturally to obtain Ni3Fe / Ni3ZnC. 0.7 Composite materials.
[0058] Contains 2.5 wt% Ni3Fe / Ni3ZnC 0.7 Preparation of Mg-based hydrogen storage materials based on composite catalysts:
[0059] Take 0.1g of the Ni3Fe / Ni3ZnC prepared in this invention 0.7 The composite material and 3.9 g of MgH2 powder were loaded into a ball mill jar at a ball-to-material ratio of 30:1 and ball-milled at 500 rpm for 10 h to finally obtain a Ni3Fe / Ni3ZnC mixture containing 2.5 wt%. 0.7 The Mg-based hydrogen storage material of the composite catalyst is designated as 2.5wt% Ni3Fe / Ni3ZnC. 0.7 And used for hydrogen storage performance.
[0060] The test results are similar to those of Example 1. This invention adds Ni3Fe / Ni3ZnC. 0.7 The catalyst exhibits significantly improved performance compared to pure MgH2.
[0061] Example 3
[0062] (1) Mix 7.5 mmol nickel acetate, 3.8 mmol ferrous acetate, 3.8 mmol zinc acetate with 150 ml N,N-dimethylformamide and stir magnetically for 0.5 h to obtain mixed solution A;
[0063] (2) Mix 9 mmol of phthalic acid, 2.125 ml of triethylamine and 100 ml of N,N-dimethylformamide and stir magnetically for 0.5 h to obtain mixed solution B;
[0064] (3) Mix the two solutions obtained in step (1) and step (2) and stir for 1 hour to obtain solution C;
[0065] (4) The C solution obtained in step (3) was vacuum filtered for 10 hours and washed three times with N,N-dimethylformamide.
[0066] (5) The precursor obtained in step (4) is calcined at a temperature of 700℃ for 10 hours under an argon atmosphere. The calcined product is then allowed to cool naturally to obtain Ni3Fe / Ni3ZnC. 0.7 Composite materials.
[0067] Contains 7.5 wt% Ni3Fe / Ni3ZnC 0.7 Preparation of Mg-based hydrogen storage materials based on composite catalysts:
[0068] Take 0.3g of the Ni3Fe / Ni3ZnC prepared in this invention 0.7 The composite material and 3.7 g of MgH2 powder were loaded into a ball mill jar at a ball-to-material ratio of 30:1 and ball-milled at 500 rpm for 10 h to finally obtain a Ni3Fe / Ni3ZnC mixture containing 7.5 wt%. 0.7 The Mg-based hydrogen storage material of the composite catalyst is designated as MgH2-7.5wt%Ni3Fe / Ni3ZnC. 0.7 And used for hydrogen storage performance.
[0069] The test results are similar to those of Example 1. This invention adds Ni3Fe / Ni3ZnC. 0.7 The catalyst exhibits significantly improved performance compared to pure MgH2.
[0070] The test results of Examples 1-3 show that MgH2-Ni3Fe / Ni3ZnC 0.7 The composite material exhibits efficient hydrogen absorption and desorption performance at low temperatures and excellent cycle stability. This invention incorporates Ni3Fe / Ni3ZnC. 0.7 The catalyst exhibits significantly improved performance compared to pure MgH2.
[0071] The above are merely embodiments of the present invention and are not intended to limit the scope of protection of the present invention. It should be noted that any modifications, equivalent substitutions, improvements, etc., made by those skilled in the art without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.
[0072] The obtained Ni3Fe / Ni3ZnC 0.7 Composite materials were characterized by X-ray diffraction, such as... Figure 1 As shown. Through interaction with Ni3ZnC 0.7 By comparing with the standard PDF card, it can be determined that the three relatively obvious diffraction peaks located at 42.8°, 49.8°, and 73.1° belong to Ni3ZnC. 0.7 Multiple diffraction peaks detected at 44.2°, 51.4°, and 75.6° belong to Ni3Fe. These results demonstrate that this method successfully synthesized Ni3Fe / Ni3ZnC. 0.7 Subsequently, the synthesized Ni3Fe / Ni3ZnC 0.7 The morphology of the composite material was characterized, such as Figure 2 As shown, numerous three-dimensionally interwoven nanotubes can be observed, surrounded by many small particles. The nanotubes exhibit random orientation, with a length of approximately 500-600 nm and a diameter of approximately 30-100 nm. These dimensions allow for the creation of a large number of hollow tubular structures with a length (500-600 nm) significantly greater than a diameter (30-100 nm), providing a larger specific surface area and significantly increasing the adhesion area of catalytically active sites, thus promoting the adsorption and dissociation of hydrogen molecules on the surface of the composite material.
[0073] The obtained MgH2-5wt%Ni3Fe / Ni3ZnC 0.7 Hydrogen absorption and desorption kinetics performance tests were conducted, and the test data are as follows: Figure 3 and Figure 4 As shown, the present invention adds Ni3Fe / Ni3ZnC 0.7 The catalyst exhibits significantly improved performance compared to pure MgH2. MgH2-5wt%Ni3Fe / Ni3ZnC 0.7 Regarding hydrogen absorption: at 353 K, the sample can absorb 4 wt% H2 within 1 h. Under the same conditions, the addition of 2.5 wt% and 7.5 wt% Ni3Fe / Ni3ZnC... 0.7 The sample can absorb 2.72% and 2.58 wt% H2; regarding hydrogen release: at 573 K, MgH2-5 wt% Ni3Fe / Ni3ZnC 0.7 The hydrogen release of the composite material within 1 hour can reach 6.25 wt% H2. Under the same conditions, the addition of 2.5 wt% and 7.5 wt% Ni3Fe / Ni3ZnC... 0.7The sample can release 1.62% and 5.0 wt% H2. This is in contrast to the obtained MgH2-5 wt% Ni3Fe / Ni3ZnC. 0.7 Cyclic performance testing was performed, and the test data is as follows: Figure 5 As shown. After twenty cycles, MgH2-5wt%Ni3Fe / Ni3ZnC 0.7 The hydrogen absorption and desorption capacity retention rates were 94.0% and 96.0%, respectively, demonstrating excellent cycle stability. Under the same conditions, it showed a significant improvement compared to pure MgH2.
Claims
1. A Ni3Fe / Ni3ZnC 0.7 Composite material, characterized in that, It consists of a large number of three-dimensionally interwoven nanotubes and surrounding small particles. The nanotubes are randomly oriented and have a bamboo-like structure. Some nanotubes are embedded with fine particles. The nanotubes are 500-600nm long and 30-100nm in diameter, while the small particles are 20-60nm in size.
2. The Ni3Fe / Ni3ZnC according to claim 1 0.7 A method for preparing composite materials, characterized in that, Includes the following steps; (1) Mix nickel acetate, ferrous acetate, zinc acetate and N,N-dimethylformamide and stir magnetically to obtain mixed solution A; (2) Terephthalic acid, triethylamine and N,N-dimethylformamide are mixed and magnetically stirred to obtain mixed solution B; (3) Mix the two solutions obtained in step (1) and step (2) and stir to obtain solution C; (4) The C solution obtained in step (3) is vacuum filtered and washed multiple times with N,N-dimethylformamide; (5) The precursor obtained in step (4) is calcined, and the calcined product is naturally cooled to obtain Ni3Fe / Ni3ZnC. 0.7 Composite materials.
3. The Ni3Fe / Ni3ZnC according to claim 2 0.7 A method for preparing composite materials, characterized in that, In step (1), the molar ratio of nickel acetate, ferrous acetate, and zinc acetate is 2:1:1, the mass ratio of nickel acetate to N,N-dimethylformamide is 1:(80-90), the mass ratio of ferrous acetate to DMF is 1:(180-200), the mass ratio of zinc acetate to DMF is 1:(170-180), and the magnetic stirring time is 0.5-1h.
4. The Ni3Fe / Ni3ZnC according to claim 2 0.7 A method for preparing composite materials, characterized in that, In step (2), the molar ratio of terephthalic acid to triethylamine is 1:(1-2), the mass ratio of terephthalic acid to N,N-dimethylformamide is 1:(60-65), the mass ratio of triethylamine to N,N-dimethylformamide is 1:(60-63), and the magnetic stirring time is 0.5-1h.
5. The Ni3Fe / Ni3ZnC according to claim 2 0.7 A method for preparing composite materials, characterized in that, In step (3), the magnetic stirring time is 0.5 to 1 hour.
6. The Ni3Fe / Ni3ZnC according to claim 2 0.7 A method for preparing composite materials, characterized in that, In step (4), the vacuum filtration time is 8 to 12 hours, and the sample is washed with N,N-dimethylformamide 3 to 5 times.
7. The Ni3Fe / Ni3ZnC according to claim 2 0.7 A method for preparing composite materials, characterized in that, In step (5), the calcination temperature is 700-800℃, the holding time is 8-10h, and the calcination atmosphere is argon.
8. Ni3Fe / Ni3ZnC prepared by the method according to any one of claims 2-7 0.7 The application of composite materials is characterized by, The Ni3Fe / Ni3ZnC 0.7 The composite material is used in hydrogen storage catalysts, namely Ni3Fe / Ni3ZnC. 0.7 The composite material is used as a catalyst and mixed with magnesium hydride powder by ball milling to form a magnesium-based hydrogen storage material.
9. The Ni3Fe / Ni3ZnC according to claim 8 0.7 The application of composite materials is characterized by, The Ni3Fe / Ni3ZnC 0.7 Composite materials account for 2.5 wt% to 7.5 wt% of magnesium-based hydrogen storage materials as catalysts.
10. The Ni3Fe / Ni3ZnC according to claim 8 0.7 The application of composite materials is characterized by, During the ball milling process, the material-to-ball ratio is 30:1, the ball milling speed is 500 rpm, and the ball milling time is 10 hours.
